PERANCANGAN PROTOTYPE PEMBANGKIT LISTRIK TENAGA BAYU DENGAN MEMANFAATKAN ANGIN EXHAUST FAN KITCHEN - Listara Wijaya, I Putu Gede; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
The largest source of energy in Indonesia, especially those currently used, mostly still come from non-renewable fossil fuels, which are not environmentally friendly because they produce ???????? 2 gas. Wind energy is a renewable energy source that is environmentally friendly. Apart from using natural wind energy, there is also artificial wind which is the result of wasted energy from exhaust fans as an alternative energy source for wind power plants (PLTB). Wind power that comes from the exhaust fan itself distributes the wind direction, so that the wind energy that can be collected into the turbine is not optimal, so it is necessary to install a wind tunnel. In this study, a trapezoidal wind tunnel model was designed with 2 different lengths, namely 50 cm and 100 cm, which were placed at the end of the fan inlet. This study aims to determine the effect of installing a wind tunnel on the wind speed of the exhaust fan and its effect on the input power of the exhaust fan. The method used in this research is a quantitative method. The research results obtained when the addition of a 50cm blower increased wind speed from 5.8m/s to 12.8m/s, the exhaust fan capacity increased by 119 watts, from 249.2 watts to 368.2 watts, when with a 100 cm fan the wind speed increased to 119 watts. increased from 5.8 m/s to 11.8 m/s, exhaust fan power increased by 70.8 watts, from 249.2 watts to 320 watts.